Diffusion Bonding of Ti6Al4V to Al2O3 Using Ni/Ti Reactive Multilayers - Silva, Marcionilo (2021)
This paper aims to investigate the diffusion bonding of Ti6Al4V to Al2 O3 . The potential of the use of reactive nanolayered thin films will also be investigated. For this purpose, Ni/Ti multilayer thin films with a 50 nm modulation period were deposited by magnetron sputtering onto the base materials. Diffusion bonding experiments were performed at 800◦ C, under 50 MPa and a dwell time of 60 min, with and without interlayers. Microstructural characterization of the interface was conducted through scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDS). The joints experiments without interlayer were unsuccessful. The interface is characterized by the presence of a crack close to the Al2 O3 base material. The results revealed that the Ni/Ti reactive multilayers improved the diffusion bonding process, allowing for sound joints to be obtained at 800◦ C for 60 min. The interface produced is characterized by a thin thickness and is mainly composed of NiTi and NiTi2 reaction layers. Mechanical characterization of the joint was assessed by hardness and reduced Young’s modulus distribution maps that enhance the different phases composing the interface. The hardness maps showed that the interface exhibits a hardness distribution similar to the Al2 O3, which can be advantageous to the mechanical behavior of the joints.